2013
DOI: 10.1089/chi.2013.0064
|View full text |Cite
|
Sign up to set email alerts
|

Parental Concerns about Weight-Based Victimization in Youth

Abstract: Background: The present study aimed to assess parental perceptions of weight-based victimization (WBV) and its consequences for children's health as well as how perceptions of WBV vary by parental and child weight status.Methods: A national sample of American parents with children ages 2-18 years (N = 918) completed an online questionnaire to assess their perceptions of how common WBV is, compared to other forms of victimization among youth, their level of concern with this issue both generally and for their o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 31 publications
1
29
1
1
Order By: Relevance
“…Subsequently, participants were asked their perceptions of how common (from 1 = very uncommon to 5 = very common) and how serious (from 1 = not at all serious to 5 = very serious) weight‐based bullying is in general. These three questions were developed and tested previously by the authors .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, participants were asked their perceptions of how common (from 1 = very uncommon to 5 = very common) and how serious (from 1 = not at all serious to 5 = very serious) weight‐based bullying is in general. These three questions were developed and tested previously by the authors .…”
Section: Methodsmentioning
confidence: 99%
“…Being overweight is one of the most prevalent reasons for peer harassment reported by youth . Both teachers and parents view weight‐based bullying as the most frequent and problematic form of youth bullying. Although most research on weight‐based teasing and bullying (‘weight‐based victimization’) has occurred in the United States, increasing studies are documenting this problem among youth globally, especially in nations with high rates of childhood obesity .…”
Section: Introductionmentioning
confidence: 99%
“…National estimates indicate that weight discrimination is among the most frequent forms of discrimination reported by adults and is comparable to rates of racial discrimination among women [1]. Among youths, weight stigma is experienced as pervasive bullying and victimization and is reported by youths, teachers, and parents to be one of the most prevalent forms of bullying that youths face at school [2][3][4][5]. In addition to numerous social consequences, economic inequalities, and psychological consequences imposed by weight stigma [6], those who experience weight bias or discrimination may be additionally vulnerable to health risk behaviors and outcomes that can exacerbate poor health and obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence from students, parents, and teachers indicates that weight-based bullying is one of the most frequent forms of bullying that youth experience at school. 12,13 A 2011 nationwide survey of over 5000 educators demonstrated that weight-based bullying was viewed to be more problematic than bullying because of a student's gender, sexual orientation, or disability. 12 In a national sample of 918 parents, being overweight was perceived to be the most common reason that youth are bullied, regardless of parents' own or their child's weight status.…”
Section: Introductionmentioning
confidence: 99%
“…12 In a national sample of 918 parents, being overweight was perceived to be the most common reason that youth are bullied, regardless of parents' own or their child's weight status. 13 One study of 1555 high school students found that being overweight was reported to be the primary reason that students observed their peers being teased and bullied at school, 14 and more recent evidence from 2793 adolescents similarly demonstrated that weight-based harassment was the most prevalent form of harassment reported by girls (38 per cent), and the second most common form of harassment among boys (32 per cent). 15 Are overweight and obese students adequately protected from weightbased bullying under existing provisions?…”
Section: Introductionmentioning
confidence: 99%